Reflections From Engaging a Network of Local Stakeholders in Discussing Training Needs for Sustainable Renovation - Simpson, Kate; Owen, Alice (Frontiers in Built Environment, 2020)
Sustainable renovation of buildings is essential to create comfortable, affordable buildings fit for the future. Sustainable renovation delivers on a triple bottom line of improving environmental, social and economic impacts. There is a clear policy driver for reducing environmental impact in the form of carbon emissions and alongside achieving this homes and communities can become more comfortable places to live, creating jobs and economic value. The purpose of this paper is to share reflections from stakeholder engagement in identifying workforce training requirements and needs to achieve sustainable renovation. The paper stems from data collected in an exploratory workshop and follow up discussions gathering multiple construction stakeholders in Leeds, UK, early 2018. Participants represented a networked system of roles including policy influencers, procurement staff, training providers, employers and skilled professionals. These stakeholders identified two areas of training need for sustainable renovation: building performance and social value. Within these two themes, we consider potential training routes in delivery as well as incentives and opportunities. We hope this reflection offers a platform for further research, training and practice in developing environmental, social and economic benefits from building renovation.